Testicular blood supply and growth in children with high cryptorchidism treated with gubernaculum preserving vs. cutting laparoscopic orchiopexy: A pilot trial. Issue 6 (December 2021) - Zhang, Jianguo; Yang, Xia; Zhang, Chao; Li, Haowei; Zhao, Yongxiang; Ku, Chaosheng; Qi, Lin; Bai, Yu; Yang, Lin; Zhang, Hailong; Yue, Dongqing; Wei, Wenfeng; et al.
Summary: Introduction: It is still controversial whether the frenum of testis should be retained in laparoscopic testicular fixation. Materials and methods: It is a prospective experiment to study testicular preservation on testicular growth in children with high cryptorchidism. Results: From January 2018 to June 2020, 120 children with high cryptorchidism in Inner Mongolia Maternal and Child Health Care Hospital and The Fourth Hospital of Baotou were randomly divided into retention group (60 cases in group P, aged 1–3 years, average 1.85 ± 0.58) and cutting group (60 cases in group C, aged 1–3 years, average 1.75 ± 0.66) (P = 0.52). PSV, EDV, RI and testicular volume were measured by color Doppler ultrasound before operation and 1, 3, 6, 12 months after operation. No, there was significant difference between the two groups (P > 0.05). Conclusions: There is no significant difference in testicular blood supply and growth between laparoscopic testicular fixation and frenulum amputation in children with high cryptorchidism.